Механізм впливу цифрової маркетингової комунікації на споживача в умовах військового стану країни - Каліна, Ірина Іванівна; Хайдарова, Тетяна Миколаївна; Сабірова, Індіра Миргазимівна (My University, 2023)
Цифровізаційні процеси в країні та на підприємствах є потужними двигунами економічного зростання, збільшення фінансових результатів та прибутку як країни так і підприємства у всьому світі. Це також допомагає підприємствам краще адаптуватися до змін, які відбуваються під впливом зовнішніх факторів. До небезпекового зовнішньо фактору віднесемо – війну. 24.02.2022 року цифрова маркетингова комунікація на споживача змінилася з новими викликами. В статті розглянули механізм впливу цифрової маркетингової комунікації на споживача який складається з трансформаційних інструментів. Одне з перших це вплив зовнішніх факторів, які змінюються та трансформуються, і з новими викликами впливають на підприємство, яке в свою чергу має адаптуватися чи гнучко реагувати на дані зміни таким чином щоб всеодно подобатися чи сподобатися споживачу. Наступне це стратегія цифрових маркетингових комунікацій, що охоплює основні позиці для формування, розробки та її провадження: визначення бізнес-цілі, цільова аудиторія, цифрова тактика, контроль, результати, ефективність. Digitization processes in the country and at enterprises are powerful engines of economic growth, increasing financial results and profits of both countries and enterprises around the world. It also helps businesses better adapt to changes that occur under the influence of external factors. War is a dangerous external factor. On February 24, 2022, digital marketing communication to the consumer changed with new challenges. The article considered the mechanism of influence of digital marketing communication on the consumer, which consists of transformational tools. One of the first is the influence of external factors that change and transform, and with new challenges affect the enterprise, which in turn must adapt or flexibly respond to these changes in such a way that the consumer is always liked or liked. The following is a strategy for digital marketing communications, covering the main points for its formation, development and implementation: definition of a business goal, which will be the foundation for the formation of a strategy; the target audience at which the strategy and goal will be aimed; digital tactics that influence choice for effective results; control by means of which problematic issues are settled; the results that show the work done and in which marketing direction to move on, the efficiency that shows the financial results of the work done. And the last is the consumer's reaction to the changes taking place in the country. Especially wartime changes and consumer choice in times of danger.
Keywords: маркетингова комунікація; marketing communication; військовий стан; martial law; споживач; onsumer